A giant 90-nucleus silver cluster templated by hetero-anions. Issue 35 (16th April 2018) - Liu, Jia-Wei; Su, Hai-Feng; Wang, Zhi; Li, Yan-An; Zhao, Quan-Qin; Wang, Xing-Po; Tung, Chen-Ho; Sun, Di; Zheng, Lan-Sun
Abstract : A giant 90-nucleus silver cluster templated by hetero-anions was isolated and characterized. Abstract : A 90-nucleus silver cluster (SD/Ag38 ) cocapped by t BuC6 H4 S − and PhCOO − ligands was synthesized using hetero-anion template method. Single-crystal X-ray diffraction (SCXRD) revealed a 90-nucleus metallic dumbbell-like core constructed by two large W5 O19 @Ag38 heads sandwiching one slender (SO4 )2 @Ag14 waist. Both W5 O19 8− and SO4 2− templates were in situ generated and synergistically induced the formation of the largest known anion-templated silver cluster. Although SD/Ag38 is emission-silent at room temperature, increasingly brighter near-infrared (NIR) emission at ca. 742 nm was detected on cooling from 293 to 93 K.